2010
DOI: 10.1061/(asce)ee.1943-7870.0000202
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Temperature Distributions in Municipal Solid Waste Landfills

Abstract: Long-term spatial and temporal variations in temperatures have been investigated in covers, wastes, and liners at four municipal solid waste landfills located in different climatic regions: Alaska, British Columbia, Michigan, and New Mexico. Temperatures were measured in wastes with a broad range of ages from newly placed to old �up to 40 years�. The characteristic shape of waste temperature versus depth relationships consisted of a convex temperature profile with maximum temperatures observed at central loca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 28 publications
6
78
0
7
Order By: Relevance
“…The temperature ranges in this study cover rather well the temperature ranges found in field conditions shown earlier and recently in [31]. As a result, when estimating long-term methane emissions from landfills, one must be cautious and select temperature coefficients carefully, based on representative data.…”
Section: Post-closure Management and Temperature Impact Coefficientsmentioning
confidence: 89%
“…The temperature ranges in this study cover rather well the temperature ranges found in field conditions shown earlier and recently in [31]. As a result, when estimating long-term methane emissions from landfills, one must be cautious and select temperature coefficients carefully, based on representative data.…”
Section: Post-closure Management and Temperature Impact Coefficientsmentioning
confidence: 89%
“…There is physical evidence of high rainfall over this time, but there was no temperature monitoring of the landfill. Hanson et al (2010) have indicated that significant temperature changes can occur in landfills over the timescale of this experiment, but there is no way of 'knowing if this occurred.…”
Section: Discussionmentioning
confidence: 99%
“…hydration of combustion ash, aluminum production waste, metallic wastes, and lime), and possible smoldering combustion (Martin et al 2013). Field measurements indicate that, depending on waste type, waste density, climate, and operational conditions, landfill temperatures can typically reach as high as 608C (Rowe 2005;Hanson et al 2010;Bouazza et al 2011). Stark et al (2012) and Jafari et al (2014) reported significantly higher temperatures (e.g.…”
Section: Temperature Effectsmentioning
confidence: 99%